Race diversity in social media branded content: Exploring audience responses - Langaro, D.; Marques, C.; Cintra, M. (EMAC Regional Conference 2024, 2024)
Purpose – Around 50% of audiences do not feel represented in advertising, due to aspects like race, gender, sexual orientation, and age. Race inclusion, in particular, expressed by the diversity of skin tone, is important given the white-skinned dominant presence. This study analyses the actual representation of diverse skin tones in publications of make-up brands on Instagram pages, examining the impact of inclusive communication regarding skin tones on audiences’ responses in terms of engagement and sentiment. The type of brand is accounted for moderating the effects. Design/methodology/approach – A content analysis of 50 Instagram posts from 15 make-up brands was conducted, with a total of 750 posts inspected. Likes, shares, and comments are analysed. Findings – Results, as expected, indicate that diversity negatively affects brand audience engagement (estimated as the number of likes, comments, and shares relative to the page audience). When the content of comments is analysed, results reveal that diversity significantly affects positive sentiment. The effects are influenced by the type of brand, with mass market brands decreasing the level of engagement significantly more than premium brands. Originality/value – This study is pioneering in exploring how audiences in social media react to skin tone diversity. Findings reveal that skin tone diversity implies less engagement, as the content is more appreciated among less diverse audiences (premium brands) than among more diverse ones (mass market brands). Implications for theory and practice are presented.